The roles of paternalistic leadership in strategic internal communication - Chan, Juan Yie (2023)
Paternalistic leadership (PL) is understudied in South-Eastern countries, particularly Malaysia, an Islamic country, and yet not many research findings have looked into its potential implications in educational settings. Therefore, this study explored the relationship between school principals’ paternalistic leadership and communication competence on teachers’ job satisfaction and communication satisfaction as well as teachers’ commitment. The enhancement of leadership roles and communication skills had eventually lead to changes in the ways teachers work and dedicate their commitment to the school. This research has been conducted using quantitative methodology. It was based on a case study of nine Chinese Independence High Schools (CIHSs) in Perak. Data were collected using questionnaires which were distributed randomly to obtain responses from teachers in the nine CIHSs in Perak. This study found that the three PL sub-dimensions had different effects on communication satisfaction and job satisfaction among school teachers. Authoritarian leadership had a negative impact on both job and communication satisfaction, but moral leadership had a favorable impact on communication satisfaction among teachers. Meanwhile, school teachers' commitment was significantly influenced by both communication and job satisfaction. Based on the results derived in this study, it has been determined that there is a need for existing school principals of CIHSs in Perak to shift their approach to paternalistic leadership and develop effective communication strategies for more effective outcomes that apply to their school structure and nature. Implications for school principals to effectively manage and maintain their school teachers by exposing them to the fundamental understanding of how teachers were affected by paternalistic leadership and leadership communication competency are also discussed.